Shaping managerial system by quality in project with use the flexible modules - Лазько, Ірина Володимирівна (Eastern-European Journal of Enterprise Technologies, 2014)
Practical experience of some institutions in the sphere of quality management proves that a model for the project quality management system is developed mainly at the discretion of the developer, and, as a rule, based only on unified standard ISO 9001:2008 without considering special features of an industry sector, and is characterized by the variety of the obtained end result, considerable labour intensity and duration. A rather formal GMS process model is built just for certification purposes, which is insufficiently adapted to the designing and engineering requirements, not flexible enough and not capable to be quickly readjusted. Such a situation encourages to conduct a study and propose an approach to building a process-oriented project QMS model which would be flexible and to the utmost take into account the requirements of QMS normative base and industry special features. For this purpose, during the study an analysis and comparison of the requirements of normative base regulating the functioning of the project quality management system were carried out. The degree of compatibility and possibility of integration of requirements of the compared standards determined by an expert method, that is from 0,7 to 0,9 (depending on comparative requirements), confirms the compatibility of the studied standards and possibility of their integration. Based on the results of assessment typical groups of processes (flexible modules) taking place in the system were identified. At that, a formalized description of a project QMS model was carried out using the mathematical modeling means, this model was synthesized using flexible modules which have constant, variable and alternative parts. The list of project QMS processes resulted from analysis and comparison allowed to propose a process-oriented model of the system, the elements of which are “Leadership”, “QMS planning”, “Effectiveness assessment”, “Quality assurance processes”, “Engineering processes”. The proposed model can be useful for a certification, as it takes into account the requirements of ISO 9001:2008, and for self-rating of an engineering company. The use of the model in practical activities will allow you to improve the effectiveness of project QMS due to clear regulation and transparency of the processes taking place, improvement of co-operation and communications during implementation of projects as well as improvement of management performance.